Estimativa de variabilidade genética de plantéis do camarão marinho Litopanaeus vannamei em laboratórios de maturação do Estado do Ceará, baseado em microssatélites e na região controle mitrocondrial - Silva, Samara Cardoso da (2007)
Shrimp is the most important commodity, by value, in the international seafood trade, while new techniques and technologies are needed to keep the shrimp farming and industry growing exponentially and with sustainability in Brazil. Shrimp farmers and aquaculture scientists will demand knowledge gathered from genetic improvement programs through husbandry and/or disease management to reduce the loss of genetic diversity in successive generations. A currently popular type of molecular marker aproach to evaluate genetic variability (both in wild and farmed populations) is microsatellites. They can be assayed more rapidly than other types of molecular markers and their high allelic nature (high polymorphism and co-dominance) means that they confer more information per unit assay than any other marker systems, thus reducing costs. Another type of marker is the sequence analysis of hypervariable segments within the mitochondrial DNA (mtDNA) control region, a set of non-coding A+T rich genes that are useful to evaluate genetic intraspecies variation. In this study, microsatellite loci and the mtDNA control region of Litopenaeus vannamei were used to estimate the genetic variability of commercial broodstocks. Expected results might help in developing strategies to fully explore the available germplasm. Broodstocks from two laboratories located in the State of Ceará were investigated using 10 microsatellite DNA loci. The genetic diversity between laboratories was indicated by the number of alleles per locus, together with the observed heterozygosity (ranging from 3,0 to 10,5 and from 0,46 - 0,84, respectively). Deviations from the Hardy-Weinberg equilibrium were found at most loci in both laboratories. Inbreeding levels have shown positive Fis values, exception made to the locus 1003 that had negative values for both laboratories. Fst values were not significantly different between the two laboratories. Analyses of multiple sequence alignment of the mtDNA control region showed high homology. Using Kimura’s two-parameter (K2P) model, a dendrogram was generated with our sequences (those obtained in this study) and wild populations’ sequences available at GenBank®/NCBI. The resulting dendrogram confirmed a good variability index in the mtDNA control region, without evidences of population differentiation among them. Accordingly, analyses of our data do indicate that cultured shrimp populations in Ceará still keep some level of genetic variability, with studied broodstocks seeming to have accumulated genetic differences.